Pulmonary embolism complicating Mycoplasma pneumoniae pneumonia in children: a retrospective case series - Tao, Pei; Wang, Zhigang; Zhou, Kaiyu; Wu, Ying (Frontiers in Pediatrics, 2026)
ObjectivesTo describe the clinical characteristics, management, and outcomes of children with Mycoplasma pneumoniae pneumonia (MPP) complicated by pulmonary embolism (PE).MethodsWe conducted a retrospective review of eight children diagnosed with Mycoplasma pneumoniae pneumonia complicated by pulmonary embolism between January 2023 and December 2024 at our hospital. The diagnosis of pulmonary embolism was confirmed by computed tomography pulmonary angiography (CTPA). Demographic characteristics, clinical manifestations, laboratory findings, imaging features, treatment strategies, and outcomes were systematically collected.ResultsThe cohort included six males and two females, with a mean age of 7.81 ± 3.64 years. The median interval from pneumonia onset to PE diagnosis was 14 days. All patients had severe or refractory MPP. Common symptoms included chest pain (n = 6), hemoptysis (n = 4), and dyspnea (n = 2). CTPA demonstrated pulmonary arterial filling defects in all cases. All patients received anticoagulation therapy with low-molecular-weight heparin followed by rivaroxaban, resulting in favorable clinical outcomes. During 3–6 months of follow-up, complete resolution of emboli was observed, thrombophilia-related laboratory abnormalities normalized, and no recurrence occurred.ConclusionsEarly diagnosis and timely anticoagulation are crucial for favorable outcomes in children with MPP-related PE. Although the small sample size limits generalizability, this case series provides a structured clinical dataset that captures demographic, laboratory, immunological, and imaging features. These data may serve as a reference for future studies aiming to better understand host susceptibility and immunothrombotic mechanisms in pediatric PE.